Screen time exposure and executive functions in preschool children - Nemanja Lakicevic; Marko Manojlovic; Elena Chichinina; Patrik Drid; Yury Zinchenko (Scientific Reports, 2025)
Abstract Increased screen time (ST) among preschool children is becoming a matter of concern globally. Although gadgets such as phones, tablets and computers might be of educational use in this population, excessive ST might impair cognitive function among preschoolers. As data on this topic in preschool children are scarce, this study sought to investigate the relationship between ST and executive functions (EFs) in this population. A total of 1016 preschool children aged 5–6 years (M = 70.8 months, SD = 4.5) were tested using the Developmental Neuropsychological Assessment (NEPSY-II) and the Dimensional Change Card Sort tests for cognitive flexibility (CF), visual working memory (WM), verbal WM, inhibition and motor persistence with parental consent, while ST was reported via a questionnaire completed by their mothers. Participants spent approximately 2 h in both active and passive ST per day, with boys spending much more time in active ST than girls. There was a very weak negative correlation between CF and both active and passive ST, and a weak negative correlation between verbal WM and both active and passive ST. Additionally, there was a very weak negative correlation between inhibition and passive ST on weekday. To ensure proper development of EFs in preschool children, ST should be limited to ≤ 1 h per day of high-quality educational/interactive content as previously determined by eminent pediatric institutions worldwide. Proven remedies that enhance EFs in children, such as physical activity and cognitive training, should be practiced regularly.